Seismic response of soil-pile raft-structure system - Saha, Rajib; Dutta, Sekhar Chandra; Haldar, Sumanta (Journal of Civil Engineering and Management, 2015)
This paper presents an initial effort to investigate seismic response of soil-pile raft-structure system considering soil-structure interaction effect. In general, structure and piled raft under seismic load are designed considering fixed base condition. However, soil flexibility may result significant changes in the response of soil-pile raft-structure system. The study considers one storey system consisting of a mass in the form of a rigid floor slab supported by four columns. The piles are modelled by beam-column element supported by laterally distributed springs and dampers. This simple model used in present study is adequately tuned to exhibit reasonably accurate dynamic characteristics while compared to the existing well accepted methodologies. The study shows that soil-structure interaction leads to considerable lengthening of period though the lateral shear in columns are not significantly changed. However, the shear in piles is significantly increased due to SSI effect as inertia of the considerable foundation mass contributes to this increase in shear of pile. Thus, neglecting SSI may lead to unsafe seismic design of piles. A parametric study encompassing feasible variations of parameters is made under spectrum consistent ground motion. Effect of uncertainty in the soil subgrade modulus on the pile and column response variability is also studied.